Effecting of Denis’s Model of Achievement and Orientation Towards Science - Naser, Ibrahim Muhi (International Journal of Psychosocial Rehabilitation, 2020)
The science subject is considered one of the important and basic subjects in the basic education level , therefore, achieving the goals of teaching science at this stage of study is very important, for this reason, the researcher tried to help the teachers of this subject in achieving these goals, especially that achieving that effort from teachers must be accompanied by the presence of positive motives and attitudes among learners to learn these topics. The researcher has found that most of the teaching methods and approaches used by teachers also do not help in developing trends and tendencies towards the subject of science, especially those related to solving mathematical problems and processes that require mathematical efforts. So, the researcher worked to solve this problem by choosing a model based on educational games, and to convert the classroom room to a place for practice, some educational games, in order to achieve the goals of the scientific subject. Therefore he used this model with the experimental group and studied some of the vocabulary of the course, while the same vocabulary of the control group was studied in the usual way and at the end of the experiment the two groups were tested with a dimensional test and it was corrected and its results were treated with the T test for two separate samples the superiority of the experimental group that was studied according to the Deans model based on educational games was also measured, and the attitudes of learners towards this material were measured by a measure of the direction prepared for this purpose before and after the experiment was carried out. It also showed the superiority of the group that studied the Deans model in this variable over the control group.